The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/mc.22694
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signature of brain cancer

Abstract: Despite advances in surgery and adjuvant therapy, brain tumours represent one of the leading causes of cancer-related mortality and morbidity in both adults and children. Gliomas constitute about 60% of all cerebral tumours, showing varying degrees of malignancy. They are difficult to treat due to dismal prognosis and limited therapeutics. Metabolomics is the untargeted and targeted analyses of endogenous and exogenous small molecules, which characterizes the phenotype of an individual. This emerging “omics” s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 234 publications
0
95
0
2
Order By: Relevance
“…Once produced, they can be measured in tissue as well as biological fluids like blood, plasma, CSF, urine and sweat. Abnormal levels of metabolites might suggest the existence of a disease process 70. At the time of this review, the HMDB lists 450 metabolites that have been identified in CSF.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Once produced, they can be measured in tissue as well as biological fluids like blood, plasma, CSF, urine and sweat. Abnormal levels of metabolites might suggest the existence of a disease process 70. At the time of this review, the HMDB lists 450 metabolites that have been identified in CSF.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In our study, we focused on gliomas, the most common form of primary malignant brain tumor, which can be subdivided into grades II‐IV in light of WHO classification. Compared with WHO Grades II‐III, which comprise LGG, GBM WHO IV bears a dismal prognosis with median survival rates of 14.6 months . The 2016 WHO classification of central nervous system (CNS) tumors combines molecular parameters and histology to define diffuse gliomas .…”
Section: Introductionmentioning
confidence: 99%
“…The study was focused on glioma, an aggressive cerebral tumor characterized by a typical poor prognosis. In glioma acidic pHe is well known to regulate proliferation, angiogenesis, immunosuppression, invasion and chemoresistance, pathophysiological processes that are at the basis of its high heterogeneity. Therefore, a robust imaging method that would allow the quantification of the glioma pHe is of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…Despite optimal treatment consisting of maximal resection followed by radiation and chemotherapy, virtually all tumors quickly recur . A feature commonly present in GBM, as in many other tumors, is the onset of a highly glycolytic metabolism with the presence of an acid extracellular microenvironment . The chaotic and irregular vasculature occurring in the tumor region leads to an unbalanced blood supply with a consequent transient or chronic hypoxia .…”
Section: Introductionmentioning
confidence: 99%